2017
DOI: 10.1136/bjophthalmol-2016-309914
|View full text |Cite
|
Sign up to set email alerts
|

Myopic glaucomatous eyes with or without optic disc shape alteration: a longitudinal study

Abstract: Significant differences in glaucomatous progression were found between eyes with and without optic disc shape alterations, particularly disc tilt. More localised and stable courses of glaucoma progression were observed in eyes with tilted optic discs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…In this study, the myopic eyes with tilted disc showed a more stable glaucoma progression than the eyes without tilted disc. Several previous studies 6,8,10,20 have reported similar results, but the mechanism is unclear. Myopic eyes are known to experience tilting of disc and deformation of lamina cribrosa (LC) during axial elongation.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In this study, the myopic eyes with tilted disc showed a more stable glaucoma progression than the eyes without tilted disc. Several previous studies 6,8,10,20 have reported similar results, but the mechanism is unclear. Myopic eyes are known to experience tilting of disc and deformation of lamina cribrosa (LC) during axial elongation.…”
Section: Discussionmentioning
confidence: 72%
“…Myopic eyes are known to experience tilting of disc and deformation of lamina cribrosa (LC) during axial elongation. 5,6,10,21 The damage of LC will not proceed any longer after the change of myopia is stabilized as an adult. 6,20 In other words, glaucomatous changes in the tilted disc eyes may be associated with myopic changes that occur during childhood or adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations